Evaluation of CFD URANS Turbulence Models for the Building under Environmental Wind Flow with Experimental Validation - K. B. Rajasekarababu; G. Vinayagamurthy; S. Selvi Rajan (Journal of Applied Fluid Mechanics, 2022)
Wind flow on and around buildings attains more importance among architectures, builders, urban planners, structural engineers, and wind engineers. Wind tunnel experiments and wind flow assessments of full-scale buildings are expensive and complex in varied terrain conditions. Hence, wind flows are extensively assessed using Computational Fluid Dynamics (CFD). By following the turbulence parameters, CFD turbulence models create the wind tunnel and atmospheric environments. No literature has till elucidated which CFD turbulence model is more suitable for predicting the terrain wind flow on and around high-rise buildings. The efficiency of the CFD models, their performance, and their accuracy must be validated with experimental results, which is indispensable before using the turbulence model in practice. Therefore, this investigation aims to validate the Unsteady Reynolds–Averaged Navier-Stokes (URANS) simulations for a setback tall building under open terrain wind conditions enclosed within the wind tunnel dimensions. The URANS simulation is accompanied with Standard k– ε, Realizable k-ε, RNG k-ε, Standard k–ω, k–ω SST and RSM. The k –ω SST and RSM turbulence models have reproduced the wind pressure coefficients observed from the wind tunnel. However, all turbulence models failed to produce the same velocity profiles at downstream recirculation, as they vary with sampling time. The transient feature, RMS (Root Mean Square), is better reproduced by RSM and k–ω SST models, while the most unsteady features like across wind spectra and eddies were captured by Realizable, RSM and SST using iso-surface. k–ω SST and RSM models predict similar results with the experiment. Where less computational time was required for the  SST, it is promising that this model provides both mean pressure and unsteady feature, encouraging more accurate simulation around the buildings.